Fungal Communities in Sediments Along a Depth Gradient in the Eastern Tropical Pacific - Rojas-Jimenez, Keilor; Grossart, Hans-Peter; Cordes, Erik; Cortés, Jorge (Frontiers in Microbiology, 2020)
Deep waters represent the largest biome on Earth and the largest ecosystem of Costa Rica. Fungi play a fundamental role in global biogeochemical cycling in marine sediments, yet, they remain little explored. We studied fungal diversity and community composition in several marine sediments from 16 locations sampled along a bathymetric gradient (from a depth of 380 to 3474 m) in two transects of about 1500 km length in the Eastern Tropical Pacific (ETP) of Costa Rica. Sequence analysis of the V7-V8 region of the 18S rRNA gene obtained from sediment cores revealed the presence of 787 fungal amplicon sequence variants (ASVs). On average, we detected a richness of 75 fungal ASVs per sample. Ascomycota represented the most abundant phylum with Saccharomycetes constituting the dominant class. Three ASVs accounted for ca. 63% of all fungal sequences: the yeast Metschnikowia (49.4%), Rhizophydium (6.9% ), and Cladosporium (6.7%). Although we distinguished a cluster dominated by yeasts and a second cluster dominated by filamentous fungi, we were unable to detect a strong effect of depth, temperature, salinity, dissolved oxygen, and pH on the composition of fungal communities. We highlight the need to understand further the ecological role of fungi in deep-sea ecosystems.